Acehnese Sufism: The Transformation of Islamic Spirituality and Social Identity from the Classical to the Contemporary Era - Basyir, Damanhuri (Prodi Studi Agama-Agama, 2025)
This study examines the transformation of Acehnese Sufism as an expression of Islamic spirituality and a foundation of social identity from the classical to the contemporary era. Aceh, known as the Veranda of Mecca, possesses a distinctive and deeply rooted Sufi tradition within the history of Islam in the Malay Archipelago. The research aims to explore how Sufi teachings and practices in Aceh have evolved, adapted, and contributed to shaping the region’s socio-political and cultural dynamics. Employing a historical-phenomenological approach, this study investigates the works of classical Sufi figures such as Hamzah Fansuri, Syamsuddin al-Sumatrani, and Abd al-Ra’uf al-Sinkili, as well as the changing role of Sufism during the colonial, post-independence, and digital eras. The findings reveal that Acehnese Sufism has transformed from contemplative spirituality into an engaged spirituality (sufisme engagé), actively participating in political resistance, post-conflict reconstruction, and digital religious movements. This revitalization demonstrates that Acehnese Sufism serves not only as a religious heritage but also as a dynamic source of moral and social identity amid the challenges of modernity. The study contributes to the broader discourse on Islam Nusantara by offering new insights into the integration of spiritual and social dimensions in the development of Islam in Aceh.